The Effectiveness of Dance Movement Therapy (DMT) and Tai Chi on Independence and Activity Daily Living (ADL) among Elderly - Sigarlaki, Heni; Mendrofa, Fery Agusman Motuho; Sonhaji, Sonhaji (Ahmar Metastasis Health Journal, 2024)
The aging population in Indonesia is facing an issue of health and productivity. Moreover, the elderly are a population group that is vulnerable to decreased independence in carrying out daily activities. Existing studies found Dance Movement Therapy (DMT) and Tai Chi Gymnastics can be effective alternative therapy in improving the independence of the elderly. However, there have not been many studies that combine these two therapies in the context of elderly care in Indonesia. This study aimed to test the effectiveness of the combination of DMT and Tai Chi Gymnastics in improving independence and Activity Daily Living (ADL) among the elderly.  This study is quasy- Experiment with pre-test and post-test nonequivalent group design. The sample in this study totalled 60 respondents (30 intervention group dan 30 control group). The participants of this study were selected based on the inclusion criteria which included the elderly with decreased functional activity. The results of data analysis showed a significant increase in the independence and moving of ADL of the elderly after receiving a combination intervention of Dance Movement Therapy and Tai Chi Gymnastics. This study is important to arrange more efforts for related stakeholders to improve the health and productivity of the elderly. Future studies can include a larger number of respondents and more independent and control variables.